A cost effective solar powered led street light - Wong, Frederick Tsun Kiong (2014)
A cost effective solar powered LED street light was designed based on the current solar powered street light installed at Masjid Nurul Huda, Kampung Gentisan, Sepanggar, Sabah, Malaysia. A new load profile is obtained based on a thirty day data collection at site utilizing motion sensor to record movement at the area. A proposed algorithm to control the LED light intensity was presented. The new load profile was processed based on the proposed algorithm. Simulation to design a new solar powered LED street light was done using the new load profile. The design uses 180W Solar Panel, with 8 x 6V (10Ah) batteries. The system has the design capability to last for 38.6 hours. Results are compared with existing solar powered LED street light and also existing mercury vapor street light. An economic analysis for 25 years is also performed to determine the cost effectiveness of the new system where the Life Cycle Cost is found to be RM 11,143.00 compared to the existing conventional design of RM 13,626.00 which is equivalent to 18.22% of cost savings.